Applying Lean, Information and Logistics Technologies in Condition of Resource Constraints of Defense Industrial Complex - T. G. Surovtseva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article discusses the main types of resources and its constraints at the enterprises of the Russian defense industrial complex. The importance of effective allocation and optimization of resources use in the context of anti-Russian sanctions and import substitution is noted. The factor of production characteristic for modern enterprises of the defense industrial complex are distinguished. Offers a possible compensation of resource constraints with the use of modern information and logistic technologies and technologies of lean manufacturing. Given examples of the use of information technologies of projects to improve production. Production diversification is considered as a possible source of industry financing. Positions system approach to solving personnel problems. Givens consideration to replacing rest types of resources with information resource. Attention is focused on the need to implement and/or modernized the information and material flow technologies available in the defense industrial complex. Modern information and lean technologies can significantly reduce the costs of all types of resources and optimize its management.